Anomia in people with rapidly evolving severe relapsing-remitting multiple sclerosis: both word retrieval inaccuracy and delay are common symptoms. Issue 2 (1st February 2020) - De Dios Pérez, Blanca; Cordova Luna, Erika; Cloutman, Lauren; Rog, David; Preston, Emma; Conroy, Paul
ABSTRACT: Background : Multiple Sclerosis (MS) is a neurodegenerative disease that produces plaques throughout the central nervous system. MS can present in four different clinical courses. Of these, Relapsing-Remitting MS (RRMS) is the main clinical course, especially at early stages of the disease. Rapidly evolving severe (RES) RRMS is a form of RRMS in which an individual has two or more disabling relapses in one year and evidence of increasing lesions on two consecutive MRI scans. MS affects the cortical and subcortical pathways of the brain leading to impairment in both physical and cognitive skills. Speech, language and communication deficits more broadly, have been acknowledged in the MS literature, but relatively little research has focused on these symptoms. Aims : To examine communication deficits in people with (RES) RRMS, with specific focus on anomic symptoms – difficulties in word retrieval, examining measures of both accuracy and latency (time intervals for accurate word retrieval). Methods & Procedures : A communication screening assessment was conducted with 100 participants with (RES) RRMS. This screening assessment consisted of the ACE-R cognitive screen, a bespoke picture naming task, reading words aloud from the National Adult Reading Test (NART) and the Pyramids and Palm Trees Test. The picture naming task obtained timed naming responses for sixty pictures of objects from the International Picture Naming Project (IPNP). Results for participants with MS (PWMS) were compared to matched neurotypical control participants (n = 40) and normative test data. Outcomes & Results : The group mean performance for PWMS was below the lower end of the neuro-typical control range for the cognitive screen and picture naming tasks. The reading aloud and semantic association mean scores were within the neuro-typical range but towards the lower end of this range. Anomic symptoms for PWMS presented as both lapses in word retrieval and reduced speed of word retrieval. Word retrieval latency was on average 26% slower for PWMS. Within the anomic symptoms, there were instances of inaccuracy (42% of participants) as well as slow naming latency (31% of participants) in retrieving words. There was evidence of mild dysarthria for 33% of participants. Regression analyses suggested the anomic symptoms were most strongly associated with semantic processing deficits. Conclusions : Anomic symptoms are common in (RES) RRMS, and present as inaccuracy as well as slow word retrieval latency. The prevalence and cognitive nature of anomic symptoms require further research across the range of presentations of MS.